Beyond a reasonable doubt: how South African courts assess eyewitness testimony in murder trials - Musabayana, Anesu Michelle Catherine (Department of Public Law, 2025)
The impact of criminal courts accepting an honest eyewitness misidentification extends beyond the theoretical considerations of the purpose of criminal trials, sentencing, and mere notions of justice. A wrongful conviction has the consequence of punishing an innocent person, while allowing a guilty person to walk free. Such a conviction negatively impacts the life of the accused, who may suffer while in prison, and experience complex and long-lasting mental and social problems as a result of their conviction. It also damages the reliability and relevance of the criminal justice system, which should be underpinned by principles of fairness and justice. Consequently, it should be of significant concern that research across decades has confirmed the inherent fallibility of human memory. But has this research filtered into the court room? To answer this question, I have conducted a content analysis of thirteen murder cases heard by the Western Cape High Court between 2007 and 2021 to consider how the Court considers the role of human memory in eyewitness testimony. Using thematic analysis, I show how the Court has appeared to weigh various factors that support and detract from a witness' reliability, how it determines the risk level presented by each factor, and how it assures itself of its finding. From this, my findings confirm both a general judicial awareness of the risk involved in accepting eyewitness identification evidence, as well as an inherent subjectivity in how the Court comes to its conclusion that is not supported by scientific evidence. As such, I recommend the development of a more precise test for reliability, as well as further study into the area.